ANALISA FRAMING PEMBERITAAN KEBIJAKAN PEMERINTAH DALAM PENANGANAN COVID-19 DI MEDIA ONLINE - HERLINA, OKTAFIANI (Jurnal Ilmiah Widya Sosiopolitika; Vol 3 No 1 (2021): MEDIA, POLITIK, DAN PANDEMI, 2021)
The coronavirus ha s caused social, economic, and phsychological effects all over the world. This virus is easy to spread and can pose a risk of death. Indonesia is one of the countries most affected by this virus. At the beginning of its appearance, the information about those overflowed in the mass media. The media inform about Covid-19 and government policies in handling the virus. This textbased qualitative research was conducted by framing analysis. Robert Entmant's framing scheme is used to describe the reality of reporting on government policies related to handling of Covid-19 in online media. The data collection techniques is through observation, documentation, and literature study. The research process is carried out by interpreting the stage of defining the problem, estimating problems, making moral decisions and emphasizing the solution. As a result, the news framing of the handling of Covid-19 was built in line with the policies conveyed by the government in the mass media. Public communication carried out by the government can determine the direction of the news narrative in the media. The policies taken by the government always have a political, economic, and health narrative. These three things become a narrative that can not be separated in the news. The media often criticize government policies which are often inappropriate and uncoordinated so they are fed up with those informations sooner. The media should be able to give hope to the public to be optimistic and enthusiastic in dealing with the pandemic situation. Keywords : Covid-19, Coronavirus, Media, Framing